2014
DOI: 10.3109/10428194.2014.916803
|View full text |Cite
|
Sign up to set email alerts
|

Widespread use of complementary and alternative medicine among non-Hodgkin lymphoma survivors

Abstract: There are few studies examining complementary and alternative medicine (CAM) use and beliefs among non-Hodgkin lymphoma (NHL) survivors. 719 NHL patients from the University of Iowa/Mayo Clinic Molecular Epidemiology Resource who completed the 3-year post-diagnosis questionnaire were included in this study. 636 (89%) reported ever using CAM, with 78% utilizing vitamins, 54% alternative therapies and 45% herbals. Female gender was associated with increased overall CAM use (P<.0001) as well as use of vitamins (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
1
11
0
2
Order By: Relevance
“…The use of complementary and alternative medicine (CAM) including relaxation techniques is growing in popularity, and it is reported that cancer survivors are more likely to use CAM than the general population [44]. Up to 89% of survivors report the use of CAM including mind-body approaches such as relaxation [45,46], choosing to do so without being advised by a healthcare professional. Hence, a proportion of cancer and lymphoma survivors may have a preference for relaxation programmes.…”
Section: Discussionmentioning
confidence: 99%
“…The use of complementary and alternative medicine (CAM) including relaxation techniques is growing in popularity, and it is reported that cancer survivors are more likely to use CAM than the general population [44]. Up to 89% of survivors report the use of CAM including mind-body approaches such as relaxation [45,46], choosing to do so without being advised by a healthcare professional. Hence, a proportion of cancer and lymphoma survivors may have a preference for relaxation programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, have shown an association between T&CM use and patients' factors, including age and education attainment. A study at the Mayo clinic showed that participants who use complementary and alternative medicines (CAM) were more likely to be female and older (>60 years; Rausch Osian, ). Similarly, it was shown in a multinational study in Europe, that CAM users were more likely to be younger, female and with a higher educational level (Molassiotis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified and documented the clinical (cancer disease) and individual (demographic) factors associated with the usage of herbal medicine in cancer. Numerous factors have been positively correlated with herbal medicine use in cancer, such as young age, high education level, high-income level, ethnicity, female gender, cancer diagnosis, longer survival period since cancer diagnosis, receiving single or multiple cancer chemotherapies, being married, completion of conventional cancer treatment, having certain cancer symptoms, cancer metastasis, and belonging to specific social groups [22][23][24][25][26][27]. However, old age, being a child, having cancer comorbidities, place of residence, and the experience of chemotherapeutic side effects are negatively associated with herbal medicine use in cancer [16,26,28].…”
Section: Introductionmentioning
confidence: 99%